A brief inventory for DSM-5 personality disorders: The development of Coolidge Axis II Inventory Plus Turkish-Short Form - Bilge, Yusuf; Bilge, Yusuf (Cumhuriyet Üniversitesi Tıp Fakültesi Psikiyatri Anabilim Dalı, 2018)
Objective: The purpose of this study is to develop a short-form of Coolidge Axis II Inventory Plus Turkish Form (CATI+TR) specific for Turkey, which assesses personality disorders in the DSM-5, and to examine the psychometric properties of this form (CATI+TR-SF). Methods: Two samples were used in the study that to be (49.8% male, 50.2% female and mean age 34.89 +/- 11.08) community sample of 648 individuals and (35.5% male, 64.5% female and mean age 31.01 +/- 10.03) clinical sample of 138 individuals. Forty-three of the participants formed the test-retest reliability sample. In the context of convergent and discriminant validity, it were applied together CATI+TR-SF to community and clinical sample of 106 persons The Structured Clinical Interview for DSM-III Axis II Disorders-Personality Ouestionnaire (SCID-II-PQ) and to community and clinical sample of 107 persons Personality Belief Questionnaire- Turkish Short Form (PBQ-TSF). Results: In the reliability study, the Cronbach's alpha for (CATI+TR-SF) was between 0.66 and 0.77 for subscales. Correlation coefficient values for test-retest reliability were between 0.77 and 0.89. With respect to Personality Disorders scales of CATI+TR-SF, an exploratory factor analysis with principal components analysis method and varimax rotation revealed a two-factor structure with eigenvalues greater than 1, explaining 64.66% of the total variance, corresponding to the two major clusters of PDs. In the convergent validity analyzes, the correlation coefficients of CATI+TR-SF subscales with PBQ-TSF subscales ranged between 0.35 and 0.64, SCID-II-PQ subscales between 0.27 and 0.78. In the discriminant validity analysis, CATI+TR-SF personality disorder scores were found to be significantly higher in favor of the clinical sample, and CATI+TR-SF was found to differentiate clinical and community samples to SCID-II-PQ (except schizoid PD). Discussion: Findings obtained because of the analyzes showed that CATI+TR-SF is a valid and reliable scale.

Bu çalışmanın amacı, Coolidge Eksen II Envanteri Plus Türkçe Formun (CATI+TR) DSM-5’teki kişilik bozukluklarını ölçen, Türkiye’ye özgü kısa bir formunu geliştirmek ve bu formun (CATI+TR-KF) psikometrik özelliklerini araştırmaktır. Yöntem: Çalışmada 648 kişilik toplum (%49.8’i erkek, %50.2’si kadın ve yaş ortalaması 34.89±11.08) ve 138 kişilik klinik (%35.5’i erkek, % 64.5’i kadın ve yaş ortalaması 31.01±10.03) olmak üzere iki örneklem kullanılmıştır. Test-tekrar test güvenilirliği için 43 kişilik öğrenci grubuna uygulama yapılmıştır. Yakınsak ve ayırt edici geçerlilik için CATI+TR-KF ile birlikte toplum ve klinik örneklemlerden 106 kişiye SCID-II-Kişilik Anketi ve 107 kişiye Kişilik İnanç Ölçeği-Kısa Türkçe Form (KİÖ-KTF) uygulanmıştır. Sonuçlar: CATI+TR-KF kişilik bozuklukları alt ölçeklerinin Cronbach alfa değerleri 0.66-0.77 arasında bulunmuştur. Test-tekrar test analizinde korelasyon katsayıları 0.77-0.89 arasındadır. Varimax döndürmesine göre temel bileşenler analizi ile uygulanan açımlayıcı faktör analizinde özdeğeri 1’den yüksek toplam varyansın %64.66’sını açıklayan iki faktörlü bir yapı ortaya çıkmıştır. Yakınsak geçerlilik analizlerinde CATI+TR-KF alt ölçeklerinin KİÖ-KTF alt ölçekleriyle korelasyon katsayıları 0.35- 0.64 ve SCID-II-KA alt ölçekleri ile 0.27-0.78 arasında değişmektedir. Ayırt edici geçerlilik analizinde CATI+TR-KF kişilik bozuklukları puanlarının klinik örneklem lehine anlamlı derecede yüksek olduğu ve CATI+TR’nin klinik ve toplum örneklemini SCID-II-KA’ya (şizoid KB dışında) benzer bir şekilde ayırt ettiği saptanmıştır. Tartışma: Analizler sonucunda elde edilen bulgular CATI+TR-KF’nin geçerli ve güvenilir bir ölçek olduğunu göstermiştir. (Anadolu Psikiyatri Derg 2018; 19(Ek sayı.2):14-21)
DSM-5 kişilik bozuklukları için kısa bir ölçek: Coolidge Eksen II Envanteri Plus Türkçe Kısa Formun geliştirilmesi
WOS: 000448930200002
Keywords: Coolidge Axis II Inventory Plus Turkish-Short Form ( CATI plus TR-SF); DSM-5; personality disorders; psychometric properties; Coolidge Eksen II Envanteri Plus Türkçe Kısa Formu (CATI+TR KF); DSM-5; Kişilik bozuklukları; Psikometrik özellikler